Potential Activated Carbon of Theobroma cacao L. Shell for Pool Water Purification in Politeknik Negeri Padang - Yetri, Yuli (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2021)
Research has been carried out to improve the quality of the yellow pool water. The water is used as a source of clean water for the academics of the Politeknik Negeri Padang, so it needs to be improved in accordance with the quality standards of clean water, and is suitable for daily use. The adsorption process was carried out using activated carbon of Theobroma cacao L. shells which was carbonated at 400oC for 1 hour and activated with H3PO4. Characterization of functional groups using Frontier Transform Infra Red (FTIR), and morphology of surface using Scanning Electron Microscopy (SEM). The quality of clean water standard analyzed is turbidity, Total Dissolved Solids (TDS), color, Total Suspended Solids (TSS), and Fe content. Functional group analysis exhibits that the activated carbon produced has a pattern of absorption with O-H, C-H, and C-O bond types. At the optimum condition of the activation process, a good adsorbent is absorbed in pool water purification at a flow rate of 5 mL/min with a mass of 2 grams. The analysis showed an efficiency decrease in turbidity value of 67%, Total Dissolved Solids (TDS) 71%, Color 97%, Total Suspended Solids (TSS) 86%, and Fe content 38%. Surface morphology of activated carbon showed the presence of pore cavities, and after the filtration process the cavities became saturated. This shows that there has been an absorption by activated carbon, so that the water becomes clear. Activated carbon of Theobroma cacao L.shell is very effective in the process of purifying pool water into clean water and fulfilling clean water standards, so it is suitable for are used.